On the use of Apiformes and Spheciformes (Insecta: Hymenoptera) populations as a management tool (Biodiversity and Conservation, 2010)
The creation of Protected Areas was one of the ﬁrst measures taken for the protection of biodiversity and it is still the most widely used. The establishment of systems to evaluate the effectiveness of the management of these areas are crucial to validate their importance for conservation and guide the managers towards their conservation goals. Aculeate Hymenoptera, speciﬁcally Apiformes and Spheciformes, gather exceptional characteristics as bioindicators and are essential to ecosystem sustainability by including key pollinators (Apiformes), contribute for the maintenance of the equilibrium between arthropod populations (Spheciformes), and also reﬂect the patterns of other taxa. Apiformes and Spheciformes suggest that Apiformes and Spheciformes communities are a suitable management tool for habitat evaluation. communities were sampled with Malaise traps in eight different habitats initially identiﬁed by habitat type (mainly vegetation). These communities were evaluated to determine if the habitats could be differentiated based on their Apiformes and Spheciformes generic communities. Apiformes and Spheciformes diversity provided limited differentiation between habitats but was able to differentiate the most disturbed habitat from the most pristine. In general, Apiformes and Spheciformes communities were different among the eight habitats. It was also possible to establish a relation between some genera and a speciﬁc habitat type. Several genera of Apiformes and Spheciformes showed a preference for the riparian galery (RLR) and a mixed woodland (COZ), providing a general idea of the ideal conditions for the development of these groups. These results